2017
DOI: 10.1016/j.red.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

With strings attached: Grandparent-provided child care and female labor market outcomes

Abstract: Grandparents are regular providers of free child care. Similar to other forms of child care, availability of grandparent-provided child care affects fertility and labor force participation of women positively. However, grandparent-provided child care requires residing close to parents or in-laws. While living close can provide access to free child care, it may also imply costly spatial restrictions. We find that mothers residing close to parents or in-laws have lower wages and that the probability of having to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Informal childcare is sometimes preferred to formal childcare because it is more flexible and is included in a larger set of exchanges in kinship and family networks (Finch and Mason, 1993; Widmer, 2010). It has been shown that childcare provided by grandparents has a positive impact on the presence of mothers in the labour market (Garcia-Morán and Kuehn, 2012; Giudici, 2015; Gray, 2005).…”
Section: Personal Network and The Transition To Parenthoodmentioning
confidence: 99%
“…Informal childcare is sometimes preferred to formal childcare because it is more flexible and is included in a larger set of exchanges in kinship and family networks (Finch and Mason, 1993; Widmer, 2010). It has been shown that childcare provided by grandparents has a positive impact on the presence of mothers in the labour market (Garcia-Morán and Kuehn, 2012; Giudici, 2015; Gray, 2005).…”
Section: Personal Network and The Transition To Parenthoodmentioning
confidence: 99%
“…Grandparental care rates vary across OECD countries. A recent study utilising data from the Survey of Health, Ageing and Retirement in Europe (SHARE) found that between 23% (Denmark) and 70% (Italy) of grandparents take care of their grandchildren age ten or below on a daily or weekly basis (García-Morán & Kuehn, 2012). The number and proportion of Australian grandparents who provide childcare to grandchildren is not known, but both are likely to be large, given that grandparents account for around half of all childcare arrangements (ABS, 2012).…”
Section: Childcare In Australiamentioning
confidence: 99%
“…It has been documented (e.g. García-Morán and Kuehn, 2017;Compton and Pollak, 2014) that the labor-force participation rate is higher for young women who live close to their parents, thereby making grandparental childcare less of an effort.…”
Section: Background and Literature Reviewmentioning
confidence: 99%